GDP Growth and the Interdependency of Volatility Spillovers - Indika Karunanayake; Abbas Valadkhani; Martin O’Brien (Australasian Accounting, Business and Finance Journal, 2012)
This paper examines the dynamics of cross-country GDP volatility transmission and their conditional correlations. We use quarterly data (1961-2008) for Australia, Canada, the UK and the US to construct and estimate a multivariate generalised autoregressive conditional heteroskedasticity (MGARCH) model. According to the results from the mean growth equations, we identified significant cross-country GDP growth spillover among these countries. Furthermore, the growth volatility between the US and Canada indicates the highest conditional correlation. As expected, we also found that the shock influences are mainly exerted by the larger economies onto the smaller economies.
Keywords: GDP Volatility; MGARCH Models; Diagonal VECH Model; Constant Conditional Correlation Model